Quantifying hominin morphological diversity at the end of the middle Pleistocene: Implications for the origin of Homo sapiens - (:unkn) unknown (My University, 2024)
Objectives The Middle Pleistocene (MP) saw the emergence of new species of hominins: Homo sapiens in Africa, H. neanderthalensis, and possibly Denisovans in Eurasia, whose most recent common ancestor is thought to have lived in Africa around 600 ka ago. However, hominin remains from this period present a wide range of morphological variation making it difficult to securely determine their taxonomic attribution and their phylogenetic position within the Homo genus. This study proposes to reconsider the phenetic relationships between MP hominin fossils in order to clarify evolutionary trends and contacts between the populations they represent. Materials and Methods We used a Geometric Morphometrics approach to quantify the morphological variation of the calvarium of controversial MP specimens from Africa and Eurasia by using a comparative sample that can be divided into 5 groups: H. ergaster , H. erectus , H. neanderthalensis , and H. sapiens , as well as individuals from current modern human populations. We performed a Generalized Procrustes Analysis, a Principal Component Analysis, and Multinomial Principal Component Logistic Regressions to determine the phenetic affinities of the controversial Middle Pleistocene specimens with the other groups. Results MP African and Eurasian specimens represent several populations, some of which show strong affinities with H. neanderthalensis in Europe or H. sapiens in Africa, others presenting multiple affinities. Discussion These MP populations might have contributed to the emergence of these two species in different proportions. This study proposes a new framework for the human evolutionary history during the MP.
Keywords: African Research